Let m = 3 - 2. Let v be 3(-3)/27-3. Solve m = 2*z - v for z.

1

Let l(n) = -2*n + 6. Let c be l(3). Let q be -2 + (1 - (-2)/2). Solve c = -f - 1 - q for f.

-1

Let f = 14 - 23. Let j = -6 - f. Solve j*t + 8 = t for t.

-4

Let j(v) = -v3 + 7*v2 - 9*v + 1. Let g be j(5). Let p be 4/g + (-7)/(-21). Solve -x = -0*x - p for x.

1

Let t be (-5)/25 + (2 - 1810). Solve -2*u + 7*u + 15 = t for u.

-3

Let f(q) = -q3 + 5*q2 + q - 2. Let d be f(5). Let l be (d/(-6))/(3/(-24)). Solve -l*x + 5 = -7 for x.

3

Suppose 15 = v - 3. Let o = v - 13. Solve o = -5*f - 20 for f.

-5

Let g be 1*(-4 - 24/(-4)). Solve -s = g*s + 3 for s.

-1

Suppose -3*f = -6*f - 2*s + 8, -2*f - s = -6. Let g(t) = t + 14. Let j be g(-14). Solve n - f = -j*n for n.

4

Let a(d) = -5*d - 6*d - 6*d2 + 16 + 5*d2. Let z be a(-12). Solve -z = 5*f + 1 for f.

-1